PENGARUH PROFESIONALISME GURU, MOTIVASI DAN KEDISIPLINAN KERJA TERHADAP KONERJA GURU HONORER SEJARAH DI SMA SE-KABUPATEN BIMA - Haryati, Tati (Sebelas Maret University (UNS), 2015)
This research aimed to know: (1) the influence of professionalism on performance in high school history teacher honorary se-Bima Regency; (2) the influence of work motivation on performance history honorary teacher at the SMA se-Bima Regency; (3) the influence of the discipline of work on performance in high school history teacher honorary se-Bima Regency; (4) the influence of professionalism, motivation and discipline work against honorary teacher performance history at SMA se-Bima Regency. This research uses descriptive quantitative methods with the korelasional approach that aims to analyse the influence among variables with variables bound. The population of this research is the honorary teacher of history at 15 schools in SMA se-Bima Regency. Sampling technique is statifel with random sampling, with the number of samples 30 honorary history teachers who already have a SK honor area. Data collection techniques using Likert scale model now. Data analysis technique used is the analysis of multiple regression, correlation, koefesien, test the determination of F and t-test.Hypothesis tests show that: (1) the variables had a significant influence of teacher Professionalism (2.546 sig. 0,017 < 0.05) honorary teacher on performance history at SMA se-Bima Regency; (2) the variable has no effect significant motivation (1.449 sig. 0,159 > 0.05) Honorary teacher on performance history at SMA se-Bima Regency; (3) the variables do not affect significantly the working discipline (2.235 sig. 0,034 < 0.05) honorary teacher of history on performance; (4) the variables of professionalism, motivation and discipline work simultaneously had a significant influence (13.618 > 0.361) against the performance of the teacher in the HIGH SCHOOL se-Bima Regency; (5) magnitude of the value of the coefficient of multiple determination R2 = 0.566 shows the magnitude of the changes in the performance history of the honorary high school teacher se-Bima Regency about 56.6% determined by variables of professionalism, motivation and discipline.This research had conclusion that teachers professionalism, motivation and discipline effect seignifikan on performance of teachers in high school honorary se-Bima Regency. From this results, donations given by the third variables on performance guru of 56.6% and 43.3% of remainder influenced oeh other factors outside of research.